2004
DOI: 10.1086/383554
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Parallaxes of 40 L and T Dwarfs from the US Naval Observatory Infrared Astrometry Program

Abstract: We present preliminary trigonometric parallaxes and proper motions for 22 L dwarfs and 18 T dwarfs measured using the ASTROCAM infrared imager on the US Naval Observatory ( USNO) 1.55 m Strand Astrometric Reflector. The results presented here are based on observations obtained between 2000 September and 2002 November; about half of the objects have an observational time baseline of Át ¼ 1:3 yr and half Át ¼ 2:0 yr. Despite these short time baselines, the astrometric quality is sufficient to produce significant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
582
4
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(633 citation statements)
references
References 55 publications
44
582
4
3
Order By: Relevance
“…Our best modelled spectra with T eff of 1002 ± 278 K is, taking into account the errors, consistent with the estimate of 1231 K from the relation of Looper et al and the value of 1200 K found by Cushing et al (2008). Our best modelled spectrum of SDSSp J125453.90-012247.4 indicates an effective temperature above 2000 K, which is much higher than that found by Vrba et al (2004) and Cushing et al (2008), but consistent (i.e. within the errors) with a temperature around 1500 K. This value is similar to the estimate of 1370 K in the relation of Looper et al…”
Section: Effective Temperaturesupporting
confidence: 91%
See 1 more Smart Citation
“…Our best modelled spectra with T eff of 1002 ± 278 K is, taking into account the errors, consistent with the estimate of 1231 K from the relation of Looper et al and the value of 1200 K found by Cushing et al (2008). Our best modelled spectrum of SDSSp J125453.90-012247.4 indicates an effective temperature above 2000 K, which is much higher than that found by Vrba et al (2004) and Cushing et al (2008), but consistent (i.e. within the errors) with a temperature around 1500 K. This value is similar to the estimate of 1370 K in the relation of Looper et al…”
Section: Effective Temperaturesupporting
confidence: 91%
“…The T4.5 dwarf 2MASS J05591914-1404488 has historically been considered enigmatic (see Vrba et al 2004). Our best modelled spectra with T eff of 1002 ± 278 K is, taking into account the errors, consistent with the estimate of 1231 K from the relation of Looper et al and the value of 1200 K found by Cushing et al (2008).…”
Section: Effective Temperaturementioning
confidence: 99%
“…We have three very wide companions with spectral types later than M5, whose number of field objects is typically lower than earlier spectral types, suggesting that those are most likely to be associated to th planet-host star (if any of these are). This result is not so surprising and in line with the conclusions of Leggett et al (2000a), Vrba et al (2004), and Kirkpatrick et al (2012). A120, page 8 of 14 separations larger than 8.3 arcmin belonging to the thin disk can not be identified reliably.…”
Section: Stability Of Wide Companionssupporting
confidence: 78%
“…First, we have estimated that the expected number of T dwarfs in the full area of our search (∼150 deg 2 around the full sample of 49 stars) is ∼1.3. We have adopted a density of 5 × 10 −3 objects/pc −3 (Burgasser et al 2003a) and an average absolute magnitude of M J ∼ 15 mag (Vrba et al 2004) for such objects, and considered that our search is limited to J = 17 mag. Secondly, we have estimated the probability that one of this object has a proper motion within 40 mas/yr of the primary's proper motion in each direction.…”
Section: A New Brown Dwarf Companion To Hip 70849mentioning
confidence: 99%
“…The luminosity uncertainty is dominated by the distance error. Within the quoted error bar, this absolute luminosity coincides with the bolometric magnitudes reported for L3-type sources by Dahn et al (2002) and with the luminosities of L3 dwarfs given by Vrba et al (2004) and Dieterich et al (2014). However, it contrasts with the higher luminosity of G 196-3 B, L = 1.86 +0.70 −0.51 ×10 −4 L⊙ (see table 6 of Zapatero Osorio et al 2014).…”
Section: Disc Modelling Approachsupporting
confidence: 88%